Magnetoresistance in Fe 0.8 Ga 0.2 thin films with magnetic stripes: The role of the three-dimensional magnetic structure - Pianciola, Betiana Noelia; Flewett, Samuel; de Biasi, Emilio; Hepburn, Carolyna; Lounis, Lounes; Vasquez Mansilla, Marcelo; Granada, Mara; Barturen, Mariana; Eddrief, M.; Sacchi, Maurizio; Marangolo, Massimiliano; Milano, Julian (American Physical Society, 2020)
Fil: Pianciola, Betiana Noelia. Consejo Nacional de Investigaciones Cientificas y Tecnicas. Oficina de Coordinacion Administrativa Ciudad Universitaria. Unidad Ejecutora Instituto de Nanociencia y Nanotecnologia. Unidad Ejecutora Instituto de Nanociencia y Nanotecnologia - Nodo Bariloche | Comision Nacional de Energia Atomica. Unidad Ejecutora Instituto de Nanociencia y Nanotecnologia. Unidad Ejecutora Instituto de Nanociencia y Nanotecnologia - Nodo Bariloche.; Argentina